MEC towards 5G: A Survey of Concepts, Use Cases, Location Tradeoffs - Hibat Allah, Belghol; Abdellah, Idrissi (Transactions on Engineering and Computing Sciences, 2017)
In recent years, there has been a new trend to push everything to a centralized cloud, triggered by virtualization and pushed by the need to reduce costs and increase suppleness. In the process, mobile operators and industry players forgot how prominent the location of the functionality is to performance, optimal use of network resources and user experience. As they progressively grasp the influence of location in wireless networks and specifically in virtualized networks they start to look for efficient ways to deploy network taking in consideration those metrics. On the one hand Distributed Cloud RAN (DC-RAN) which consists in deploying Base Band Units (BBUs) in distributed way instead of pooling the units at centralized data center and Multiple-access Edge Computing (MEC), Previously known as Mobile Edge Computing which consists in mixing the IT & Telco domains and bringing their capabilities within the close proximity of mobile subscribers to better serve them are gaining acceptance in mobile networks. On the other hand, Software Defined Networking (SDN) and Network Function Virtualization (NFV), two promising concepts are expected to take mobile networks to a high level of agility. While SDN is based on the separation of control and data planes, NFV separates software from hardware enabling flexible network deployment and dynamic operation. Virtualization, originally used as the support for shifting to the centralized cloud, is even more basic in permitting hybrid models because it offers service providers the chance to choose a location, hardware, and software separately to optimize end-to-end network performance and Quality of Experience (QoE). In this perspective, NFV, SDN, DC-RAN, and MEC in distinct but in complementary ways man up the necessity to put processing and storage where it’s suitable to preserve a healthful harmony between what lingers centralized and what have to be distributed to the edge based on parameters such as applications, traffic type, and network conditions. In this paper, we will present MEC use cases that have gained an attraction to date and we will shed the light on the importance of the edge location and criteria to take in consideration while deploying MEC within network along with the MEC location tradeoffs.